The Use of Medicinal Herbs in Aquaculture Industry: A Review - Irwan Effendi; Dessy Yoswaty; Henni Syawal; Brian Austin; Alastair Robert Lyndon; Ronal Kurniawan; Sri Wahyuni; Ahmed Al-Harbi (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
Fish from the aquaculture industry will continue to be one of the mainstays in meeting human animal protein needs. Various global challenges face the aquaculture industry. Starting from the issue of environmental degradation, water pollution, conversion of agricultural land and aquaculture, to diseases attacks and the use of antibiotics to control fish pests and diseases. The presence of antibiotics and insecticides in food is no longer acceptable. Therefore, it is necessary to find an environmentally friendly solution for this disease and disturbance of water and environmental pollution. The use of natural ingredients in the form of medicinal plants to increase fish immunity and treat infectious diseases is a promising option. Water and environmental pollution are increasingly inevitable and the use of plants for the bioremediation process is the right choice. This paper presents a review of research on the use of several plant species that may be used for the purposes of improvement of fish immunity, enhancement of antimicrobial activity, replacement of the role of antibiotics, improvement of fish growth, improvement of feed conversion, and water quality improvement of polluted waters.